Efecto de los tipos de extractos de moringa oleífera y Caesalpinia spinosa como agente coagulante en jugo de naranja - Rizzo Ponce, Jenniffer Belén (2020)
The present investigation had like objective to evaluate extracts of M. oleífera seeds and C. spinosa leaves on the coagulant effect in orange juice. The methodology was based on finding the treatment with coagulant effect by jar test and valued by the turbidity removal in NTU; the variables were types of extracts: moringa seeds and guarango leaves; doses: 500, 1 000 and 1 500 ppm and time: 7, 24, 32 and 48 hours; having a total of 36 treatments, to which an experimental design of A*B*C with three repetitions was applied. An ANOVA with 95% confidence and Tukey and Dunnett's test was performed. The results of the turbidity showed that all the applied treatments generate the coagulant effect whit a p ˂ 0, 05. The mean comparison analysis with Tukey of each factor showed that in extracts there is a difference between moringa, guarango and the mixture M+G; while these last two were similar; the doses between them didn't present significance, being able to choose any; the time after 24 hours didn't show significant variability. In relation to pH, a little increase was observed and the °Brix decreased, staying within the range allowed by the regulations. Concluding that the best treatment was T16 whit extracts of M+G, in 500 ppm at 24 hours, removing 80, 51% of the turbidity in the orange juice.